NILAI PENDIDIKAN DALAM Q.S. Al MUJADILAH:11 - Latifah Sa’diyah; Uli Karomah; Emawati Dewi Astuti; Muhammad Syaifullah (CV. ADIBA AISHA AMIRA, 2025)
It might be difficult to benefit from learning since people occasionally forget the lessons they have learned. Due to several reasons that convey the perception that students are not benefiting from their studies, they are unable to recognize the value of knowledge. According to Q.S. Al- Mujadilah verse 11, this essay explores how to acquire noble dignity through knowledge. Islam, which strongly appreciates and praises knowledge, would have a profound impact on people who study and have that information. People can easily live their life if they have knowledge. All of the data used in this paper was gathered through library research, including books, articles, other discourse materials that connected to the study's issue. The findings of this study allow us to draw the conclusion that knowledge and study are really admirable attributes. Allah says that people who have faith and wisdom will be elevated in rank in Q.S. Al-Mujadilah verse 11. Therefore, knowledge is another means of achieving noble dignity. When someone seeks knowledge sincerely, with Allah's desire, and passionately Faith is the main goal of life, and knowledge is the means to achieving it, thus they both must work together to reach lofty dignity.